Optimization of the ultrasonic-microwave assisted enzymatic hydrolysis of freshwater mussel meat - Zhou, Yajun; Yi, Xiaoli; Wang, Jingya; Yang, Qi; Wang, Shujie (International Journal of Agricultural and Biological Engineering, 2018)
In the present study, the Ultrasonic-Microwave (US-MW) technique was applied for assisting enzymatic hydrolysis of freshwater mussel meat. The operating parameters of enzymatic hydrolysis were investigated and the properties and qualities of the freshwater mussel hydrolysates were also analyzed. The considerable optimum conditions for enzymatic hydrolysis of mussel meat were ratio of liquid to material of 10.36:1, power of 360.52 W, processing time of 6.91 min, enzymolysis time of 4 h. Under these conditions, a degree of hydrolysis (DH) of 48.40% was obtained. The hydrolysates produced under optimum conditions, were characterized in terms of electrophoretic profile, amino acid composition and infrared spectrum analysis. SDS-PAGE profiles of the hydrolysates revealed that several protein bands were cleaved and several light myosin chains (25 kDa and 15 kDa, respectively) and peptides of molecular weight lower than 6.5 kDa were identified. The infrared spectrum absorption peak of amide band A and band III shifted after US-MW pre-treatment, which indicated that the N-H (hydrogen bonding) stretching vibration and triple helix structure of samples were affected. The essential amino acids in hydrolysates with or without US-MW pre-treatment were 36.62 mg/100 g and 33.40 mg/100 g. It was proved that US-MW assisted enzymatic hydrolysis is an effective technology to utilize freshwater mussel meat.Keywords: ultrasonic-microwave (US-MW), freshwater mussel meat, enzymatic hydrolysis, degree of hydrolysis (DH)DOI: 10.25165/j.ijabe.20181105.4104Citation: Zhou Y J, Yi X L, Wang J Y, Yang Q, Wang S J. Optimization of the ultrasonic-microwave assisted enzymatic hydrolysis of freshwater mussel meat. Int J Agric & Biol Eng, 2018; 11(5): 236–242.